Analisis Perilaku Konsumen Kopi di Kecamatan Medan Selayang - Purnama, Andika; Listiyani, Listiyani; Kurniawati, Fitri (Universitas Islam Kadiri, 2025)
The research aims to determine consumer characteristics and factors that influence consumer behavior in coffee shops and coffee shops in Medan Selayang District. The method used in this study was a qualitative descriptive method. The sampling technique was purposive sampling with a total sample taken of 15 people at the coffee shop and 15 people in the coffee shop. Methods of data collection using observation, interviews and questionnaires.Data analysis in this study used descriptive qualitative which was quantified.The results of the research on the characteristics of consumers in coffee shops are that the average age is 20 years, dominated by men, the average education level is high school, employee work, income is IDR 3,300,000 with a moderate social level.The characteristics of consumers at the coffee shop are the average age of 21 years, dominated by men, the average education level is high school, employee work, income Rp. 3,283,333 with a moderate social level. Coffee consumer behavior at coffee shops is influenced by 82% personal factors, 82% psychological factors, 76% social factors and 69% cultural factors. Coffee consumer behavior at coffee shops is influenced by personal factors 79%, social factors 77%, psychological factors 71% and cultural factors 65%